(untitled) (Reumatismo, 2025)
We present a case of interstitial lung disease arising in the course of antisynthetase syndrome (ASSD) in a patient with axial spondyloarthritis (ax-SpA) undergoing tumor necrosis factor-α (TNF-α) inhibitors therapy. Only two cases of ASSD in ax-SpA patients have been described in the literature, although with a different autoantibody profile. Only in one case, ASSD manifested with lung involvement, without the possible implication of TNF-α inhibitors in the pathogenesis, as it occurred concurrently with spondyloarthritis. Our case is the first to emphasize the coexistence of ASSD with anti-glycyl tRNA synthetase antibodies and ax-SpA, reminding us of the possible, although rare, adverse effects on the lungs with TNF-α inhibitors.